Maintenance therapy: a two year comparison between Caved-S and cimetidine treatment in the prevention of symptomatic gastric ulcer recurrence. Issue 6 (June 1985) - Morgan, A G; Pacsoo, C; McAdam, W A
Abstract : Eighty two patients with an endoscopically healed gastric ulcer, were treated for two years with either Caved-S tablets, two twice daily or cimetidine 400 mg at night. During the first year, 12% (four out of 34) of the Caved-S group and 10% (four out of 41) of the cimetidine group had an ulcer recurrence. By the end of the second year, the recurrence rate was 29% (nine out of 31) in the Caved-S group, and 25% (eight out of 32) for the cimetidine group. Ulcer relapse occurred frequently in patients with either a dyspeptic history of over six months (p less than 0.05), or a past history of a gastric ulcer (p less than 0.001). Ulcers recurred rapidly after maintenance therapy; Caved-S two out of 22; cimetidine seven out of 23, within four months (NS). This study shows that long term maintenance therapy is safe and reasonably effective. The high recurrence rate after stopping treatment suggests that therapy in high risk or elderly patients should be for life.